Closely spaced rectangular footings on sand over soft clay with geogrid at the interface. Issue 4 (1st August 2018) - Saha Roy, S.; Deb, K.
Abstract : In this study, laboratory-scale experiments are carried out to investigate the interference effect on bearing capacity and settlement behaviour of two closely spaced identical footings placed on the surface of a sand layer of limited thickness underlain by a soft clay layer with geogrid at the interface. Three pairs of model footings of different sizes are used in the study. The width ( B ) and length ( L ) of the footings are chosen in such a way that the L / B ratio (aspect ratio) of the footings is varied as 1.0 (square), 1.5 (rectangular) and 2.0 (rectangular). It has been observed that there is an optimum spacing where the bearing capacity of the interfering footing reaches the maximum value. The optimum spacing is found to be 2.0 times the width of the footing for all shapes of footings at H / B  = 0.75, where H is the thickness of sand over soft clay. The maximum interference factor for bearing capacity (for a square footing) in homogeneous reinforced sand is 18% more than the sand-clay layered soil. The influence of footing interference increases with an increase in L / B ratio. The strain distribution along the reinforcement is also investigated and it is found that the strains in the reinforcement vary with the spacing ratio.